The Role of RUDEKA Community in the Internalization of Qur’anic Values among Persons with Disabilities - Rosyid, Asyhad Abdillah; Putri, Lintang Dewi Fi’liya; Amalia, Sifwah Kholilah (Sekolah Tinggi Agama Islam Taruna Surabaya, 2026)
Qur’anic education plays a vital role in shaping human religiousity, including for persons with disabilities who often face limited access to the law, public policy, and common, inclusive religious learning. The goal of this study is to describe the process of internalizing Qur’anic values among people with disabilities and to analyze the role of the RUDEKA Community in Jombang in supporting this process. This research uses a qualitative case-study approach to examine the RUDEKA Community in Jombang City. Data were collected through interviews with 2 (two) community founders, volunteers, and persons with disabilities who are members of the community, observations, and documentation of various community activities. Research findings reveal that Qur’anic values such as ṣabr (patience), syukr (gratitude), muhasabat al-nafs (self-awareness), Musyawarah (deliberation), ta‘awun (mutual help), al-musawat (egalitarianism), and ukhuwah Islamiyah are internalized through artistic expression, spiritual reflection, and participatory learning. These processes strengthen self-confidence, mental resilience, self-acceptance, spiritual independence, and social solidarity among persons with disabilities. The study concludes that collaboration between communities, persons with disabilities, volunteers, families, and Islamic educational institutions is essential to implement inclusive and humanistic Qur’anic education for persons with disabilities.